ANALISIS IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) (STUDI PADA PROGRAM TJSL PT ANGKASA PURA II (PERSERO) PERIODE 2021) - Nur'aqil, Ariiq Naufal; Rohman, Fatchur (Journal of Development Economic and Social Studies, 2022)
The goal of Corporate Social Responsibility (CSR) is to ensure company sustainability by improving the social and environmental wellbeing of areas around the company. PT. Angkasa Pura II (Persero) is a company engaged in airport business committed to CSR implementation to protect the environment from the negative impact of their operation and development. The objectives of this qualitative descriptive research are to identify CSR activities conducted by the company, to identify problems related to their CSR activities, and to find the solutions for the problems. The data was collected through interviews, observations, and documentations. This study finds that the company have run their CSR programs, but their maximum impact is reduced due to some problems such as partners who do not pay the partnership program dues, Covid-19 pandemic that influence budgets for Environmental Conservation Program, and CSR activities made by the Ministry of State-Owned Enterprises whose locations were not included in the company’s operational regions.